Lectotypification of Carex buekii (Cyperaceae) - Jimenez-Mejias, Pedro; Martinetto, Edoardo; Esser, Hans-Joachim; Soldano, Adriano (Phytotaxa, 2014)
Carex buekii Wimmer (1852: 83) is the name currently applied to a species belonging to Carex sect. Phacocystis Dumortier (1827:146) (Cyperaceae) that occurs throughout Central-Eastern Europe to SW Asia (Chater 1980, Egorova 1999, Jiménez-Mejías & Luceño 2011a, 2011b, Koopman 2011).